Internationalisation of Russia's Gazprom - Andreas Heinrich (Journal for East European Management Studies, 2003)
This article explores the specific features of the institutional environment and their implications for business operations of Russian companies on foreign markets. The author gives some insights into the relationships between internationalisation and firm behaviour. In order to analyse how and how far internationalisation can influence enterprise behaviour, this article deals with the business activities of the Russian gas monopoly Gazprom on foreign markets. It hypothesises that the different institutional settings on the various markets influence the enterprise behaviour of Gazprom, i.e. that internationalisation disseminates international norms and practices. – – Der Artikel beleuchtet die spezifischen Merkmale der institutionellen Umgebung und ihre Verwicklungen für Geschäftshandlungen von russischen Unternehmen auf ausländischen Märkten. Der Autor gibt Einblick in die Beziehungen zwischen Internationalisierung und Firmenverhalten. Zwecks der Analyse, wie und inwieweit Internationalisierung das Unternehmensverhalten beeinflusst, behandelt der Artikel die Geschäftstätigkeiten des russischen Gasmonopolisten Gazprom in ausländischen Märkten. Er stellt die Hypothese auf, dass die unterschiedlichen institutionalen Bedingungen auf den unterschiedlichen Märkten das Unternehmensverhalten von Gazprom beeinflussen, d.h., dass Internationalisierung die Verbreitung von internationalen Normen und Praktiken zur Folge hat.
Keywords: 650; Russia; Gazprom; institutional environment; export; strategic partnerships; internationalisation process